Relationship of Knowledge About Cervical Cancer and PAP SMEAR with Early Detection Behavior of PAP SMEAR - Rahmi Syahputri; Sony Sugiharto (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Cervical cancer is the third leading cause of death in Indonesia. Cervical cancer is usually only diagnosed when the cancer has entered an advanced stage. So the need for early detection as an effort to prevent cervical cancer. One of the most effective and commonly used methods to detect cervical cancer is Pap smear. The purpose of this study was to see the relationship between knowledge about cervical cancer and Pap smear with Pap smear early detection behavior. This study used analytic method with quantitative approach. The population of this study were all married women in Pancoran District, South Jakarta. Then, consecutive non-random sampling technique was used and 153 respondents were obtained with a questionnaire as a tool to obtain research data. Data collection was carried out from September to November 2023. Followed by analysis with the Chi-Square test using SPSS. Based on the results of the study, 58.2% of respondents have good knowledge and 72.5% of respondents have not done Pap smear examination from 158 respondents, there is no significant relationship between knowledge about cervical cancer and Pap smear with Pap smear early detection behavior (p-value=0.093). The conclusion of this study is that there is no relationship between knowledge about cervical cancer and Pap smear with early detection behavior of Pap smear in Pancoran District, South Jakarta. For further research, it is recommended to provide insight into cervical cancer in depth so that readers are aware of the importance of early detection of cervical cancer. Keyword: Cervival cancer, Knowledge, Pap smear